Memperkuat Koneksi Akademik dan Pengalaman Lintas Budaya melalui Program “Bridging Asian Minds: Vietnam Experience”: Strengthening Academic Connections and Cross-Cultural Experiences through the “Bridging Asian Minds: Vietnam Experience” - Hendy Endarwan; Gary Putra Etwanto; Tiolina Evi (Jurnal Bisnis dan Ekonomi, 2025)
Objective: The academic and cultural exchange between the University of Economics and Finance (UEF), Ho Chi Minh City, Vietnam, and the Perbanas Institute, Indonesia, held from August 8–9, 2025, was a huge success. The program, themed "To Bridging Asian Minds: Vietnam Experience with UEF," aimed to strengthen cross-border academic networks, broaden research horizons, and deepen cultural understanding.Methodology: The series of activities included a scientific seminar on sustainable development in the ASEAN region, an interactive discussion on the application of ESG in the banking sector, a visit to a company developing a sustainable industrial park, and an exploration of cultural and historical sites in Ho Chi Minh City and Tay Ninh.Research Findings: The results of this collaboration demonstrate that it effectively builds knowledge bridges, strengthens institutional relationships, and fosters the internationalization of sustainable education in the Asian region.Keywords: Academic exchange, internationalization of education, sustainable development, ESG, cross-border cooperation